Forgiveness in the case of a contract with a cofideiusso guarantee - León Barandiarán, José (1972)
This paper analyzes the effects of the partial debt forgiveness and its scope with respect to the obligations of guarantors provided for in the Civil Code. In this sense, the author analyzes how the joint and several scope of a debt waiver of a guarantor develops in view of the existence of other guarantors and the obligations assumed in their role as guarantors. In this way, the author also analyzes the figure of the assent between guarantors to establish his position regarding the reduction of the amount to which the guarantors are obliged or the assumption of the total amount owed.